Domestic hot water-an energy approach. Application of heat pumps for residential apartment buildings. - Rocheron, Caroline (My University, 2012)
Heat pumps for production of Domestic Hot Water are getting more and more common in residential apartment buildings because of their interesting coefficient of performance. In order to increase energy savings, not only the heat pump but the whole system was considered - from the energy source to the production and distribution systems and finally the usage. In the current project, three systems have been analyzed to produce hot water for residential apartment buildings. The goal was mainly to achieve a consumption of less than 15kWh of primary energy per square meter per year, while caring about the comfort and the cost for the user. The first system is a gas production with half accumulation storage defined like the reference technology used in most of the residential apartments in France. This system was used later to assess the performance of two other heat-pump-based systems based on outside air, solar preheating, and use of the grey water heat. The evaluation tool was the software package TRNSYS. The analysis of the systems was based on a definition of Domestic Hot Water demands previously performed by CTSB where this Master’s thesis was performed. Therefore, the systems could be assessed for different water draws and weather files. The results showed that the insulation of both storage and distribution is an essential parameter in the process of energy savings, especially in the case of a water circulation. Fumed silica and polyurethane allow for a significant reduction of heat losses and are a good compromise between heat loss reduction and investment cost. Special attention is required in the case of a variable compressor power, since a better insulation of the storage increases the water temperature of the tank and then decreases the heat pump performance. In those systems, it seems more appropriate to insulate the distribution better. This technology is in any case particularly relevant in the process of reducing energy consumption, since adapting the compressor power to the load will avoid permanent relaunching of the compressor. In summary, the goal of 15kWh/m² per year is quite ambitious, even more so when considering financial issues. The two systems studied here showed that they could achieve this performance with the main measures of insulation and compressor power adaptation. The use of free energy combined with an accumulation system enables both to reduce the energy consumptions and to delay the drawing time from the production time. However, this analysis has been done mainly from an energetic point of view; it would be of further interest to analyze the results from a manufacturer’s perspective to examine the feasibility of the recommended measures, and against the opinion of the electricity producer in terms of electricity’s peak demand erasing.
Keywords: Byggnadsteknik; Building Futures; Building engineering; Building Futures